Effects and Safety of Non-Pharmacological Therapies of Traditional Chinese Medicine for Coronary Heart Disease: An Overview of Systematic Reviews. (19th March 2022) - Ji, Weiqiang; Wu, Lan; Pan, Guangming; Zou, Xu
Abstract : Objectives . Coronary heart disease (CHD) is currently the leading cause of human death. Non-pharmacological therapy of traditional Chinese medicine (NPTCM) is an important characteristic therapy of traditional Chinese medicine (TCM). Questions concerning the efficacy and safety of NPTCM-related interventions in patients with CHD led us to conduct this overview of systematic reviews (SRs). Methods . The Cochrane Library, PubMed, Embase, EBSCO, Epistemonikos, PROSPERO, CNKI, Wanfang Database, and SinoMed were searched without language and publication status restriction from their inception to May 2021, along with grey literature sites and reference lists of included reviews. Systematic reviews comparing NPTCM/a combination of NPTCM and non-TCM interventions with non-TCM interventions/inactive controls for CHD were examined. Two reviewers independently screened titles, abstracts, and full-text articles, and completed data extraction and quality appraisal according to the predefined standards. Results . In total, 1494 titles and abstracts and 66 full-text articles were screened, and a total of 12 SRs (11 with meta-analysis) were finally included. According to PRISMA 2020 checklist, more than 50% of reviews conformed to 80% of 54 items. Consistent evidence of effectiveness or harms across multiple outcomes based on more than one moderate quality review with meta-analysis was found for acupuncture and usual care plus acupuncture/Baduanjin/TCM exercise therapies/TCM emotional therapy. These interventions were mostly evaluated less than 6 months. Conclusion . Acupuncture or acupuncture plus usual care could improve angina symptoms and ECG, and usual care plus Baduanjin/TCM exercise therapies could ameliorate health-related quality of life. Additionally, Baduanjin plus usual care could also improve psychological condition, and it as well as acupuncture could be safe due to no reports on adverse events related to these interventions. TCM emotional therapy plus usual care could benefit patients with CHD and depression.